Moringa Leaf Extract as a Natural Intervention to Increase Hemoglobin Levels in Postpartum Anemia - Reni Yuli Astutik; Suci Anggraeni; Nining Istighosah; Januaris Auktovitis (Journal Of Nursing Practice, 2025)
Background: Postpartum anemia is a significant health problem that contributes to maternal morbidity and mortality. It is estimated that 50–80% of women experience anemia within 48 hours after childbirth. In Indonesia, postpartum anemia is among the leading causes of maternal mortality. Effective and affordable interventions are urgently needed to improve maternal outcomes. Moringa (Moringa oleifera) leaves are rich in iron and essential nutrients that may support hemoglobin synthesis. Purpose: This study aimed to evaluate the effect of Moringa leaf extract on hemoglobin levels in postpartum women with anemia. Methods: A quasi-experimental study was conducted among postpartum women diagnosed with anemia. Participants were divided into an intervention group receiving Moringa leaf extract and a control group receiving standard care. Hemoglobin levels were measured before and after the intervention. Data were analyzed using paired and independent statistical tests with a significance level of p<0.05. Results: The intervention significantly improved hemoglobin levels, with the mean rising from 8.65 g/dL pre-test to 10.93 g/dL post-test (p < 0.05). The average increase of 2.27 g/dL was accompanied by a more uniform distribution, indicating effective enhancement of maternal hemoglobin status after intervention. Conclusion: Moringa leaf extract is effective in increasing hemoglobin levels among anemic postpartum women. This low-cost, natural intervention can be considered as a complementary strategy in the management of postpartum anemia, particularly in low- and middle-income settings. Further large-scale randomized controlled trials are recommended to confirm these findings.